Whole Transcriptome Analysis of Chicken Bursa Reveals Candidate Gene That Enhances the Host’s Immune Response to Coccidiosis - Guo, Lijin; Huang, Weiling; Tong, Feng; Chen, Xiaolan; Cao, Sen; Xu, Haiping; Luo, Wei; Li, Zhenhui; Nie, Qinghua (Frontiers in Physiology, 2020)
Coccidiosis is a major hazard to the chicken industry, but the host's immune response to coccidiosis remains unclear. Here, we performed Eimeria coccidia challenge in 28-day-old ROSS 308 broilers and selected the bursa from the three most severely affected individuals and three healthy individuals for RNA sequencing. We obtained 347 DEGs from RNA-seq and found that 7 upregulated DEGs were enriched in Cytokine−cytokine receptor interaction pathway. As the DEGs with the highest expression abundance in these 7 genes, TNFRSF6B was speculated to participate in the process of host’s immune response to coccidiosis. It is showed that TNFRSF6B can polarize macrophages to M1 subtype and promote inflammatory cytokines expression. In addition, the expression of TNFRSF6B suppressed HD11 cells apoptosis by downregulating Fas signal pathway. Besides, TNFRSF6B-mediated macrophages immunity activation can be reversed by apoptosis. Overall, our study indicates that TNFRSF6B upregulated in BAE, is capable of aggravating the inflammatory response by inhibiting macrophages apoptosis via downregulating Fas signal pathway, which may participate in host’s immune response to coccidiosis.